Evaluation of air pollution in Malaysia based on haze phenomena from 2000 to 2019 using satellite database / Zafirah Muhamad Haitamin and Dr. Norhusna Mohamad Nor - Muhamad Haitamin, Zafirah; Mohamad Nor, Norhusna (2020)
Air pollution in Malaysia based on haze phenomena from year 2000 to 2019 by using satellite database was evaluated. Haze phenomena is a phenomenon that happened almost every year in Malaysia. Usually, the pollutants emitted from haze were based on API readings that was provided by DOE using API. For this research work, satellite database was collected to compare the correlations between ground-based data and remote sensing data. The satellite database used was from GIOVANNI which was a portal that accommodates multiple satellite sensors that provides various parameters which some of them were haze pollutants concentrations (PM2.5, SO2, CO, Ozone). The study areas selected for both ground-based and satellite database collected were at Sarawak and Sabah as some of the hazardous and worse haze pollutant concentrations values are at these study areas. For data analysis, linear regression analysis was conducted between ground-based data and remote sensing data to find out the correlation and relationship of the model. The linear regression analysis was done using Microsoft Excel and from that analysis, R and p values were obtained to find out how strong the correlation coefficient and statistical significance of the linear models. The R values ranged from weak, moderate to strong relationship while all the p values obtained are below 0.05 which meant that the analysis of the model was statistically significance. The factors that contributed to haze phenomenon was also investigated by collecting meteorological data such as wind speed and surface temperature and it can be concluded that both factors have a strong inversely proportional relationship with haze pollutions.